Vanadiyli katalizatorlarni qayta ishlagandagi qattiq chiqindidan yangi katalizator tashuvchisini tayyorlash texnologiyasini yaratishga doir (SCIENCE and SOCIETY, 2025)
Catalysts containing vanadium pentoxide used in sulfuric acid production were recycled and utilized us- ing the hydrometallurgical method. The resulting solid waste was used as a carrier for the production of a new catalyst. The physicochemical properties of catalysts synthesized based on solid waste were studied hardened at 600°C.